Constraints on Gas Hydrate Distribution and Morphology in Vestnesa Ridge, Western Svalbard Margin, Using Multicomponent Ocean‐Bottom Seismic Data - Singhroha, Sunny; Chand, Shyam; Bünz, Stefan (Journal of Geophysical Research: Solid Earth, 2019)
Source at https://doi.org/10.1029/2018JB016574 . ©2019. American Geophysical Union. All Rights Reserved. Gas hydrates occur within sediments on the western Svalbard continental margin and the Vestnesa Ridge, a large sediment drift that extends in a west‐north‐west direction from the margin towards the mid‐ocean ridge. We acquired multi‐component ocean‐bottom seismic (OBS) data at ten locations on the crest area of the eastern segment of the Vestnesa Ridge, an area with active gas seepage. P and S‐wave velocities are estimated using travel time inversion, and SCA/DEM rock physics modeling is used to estimate gas hydrate and free gas saturation at OBS stations. We apply 1‐D Full Waveform Inversion (FWI) at a selected OBS station to study detailed variations of P‐wave velocity near the BSR. High interval P‐wave velocity (Vp≈1.73‐1.82 km/s) and S‐wave velocity (>0.35 km/s) are observed in a layer above the BSR and low interval P‐wave velocity (Vp≈1.28‐1.53 km/s) in a layer below the BSR. We estimate 10‐18% gas hydrate and 1.5‐4.1% free gas saturation at different OBS stations in a layer above and below the BSR, respectively. We find significant variation in gas hydrate and free gas saturation across faults suggesting a structural control on the distribution of gas hydrate and free gas in the Vestnesa Ridge. Differences in gas hydrate saturation derived from P‐wave velocities and earlier estimates obtained from electromagnetic surveys indicate the presence of gas hydrates in faults and fractures. Moreover, beneath some OBS sites, the combined study of P and S‐waves, resistivity and seismic quality factor (Q), suggests the co‐existence of free gas and gas hydrates.